Sandwich Panel Board Using Coconut Fibre and Fiberglass - Mohd, Ain Nur Nabihah; Samsudin , Anis Natasha; Abdul Ghapar, Noor Hafizah; Norhayati Ngadiman, (Multidisciplinary Applied Research and Innovation, 2023)
This study focus on the coconut fibre wasted in our daily life. Therefore, recycling is a suitable way to reduce coconut fibre waste. Based on the previous study, coconut fibre waste is also suitable for production of panel boards apart from for agricultural purposes. The production of panel boards from coconut fibre is not suitable as an outer layer due to its non-waterproof properties. It should be produced in the form of sandwiches. Therefore, to make the outer layer of the panel board, the material chosen must have a high density that is material does not absorb water. The most suitable material is fiberglass panel board. The objectives of this study are to produce sandwich panel board using coconut fibre panel board and fiberglass panel board by layering method. Next, to test Modulus Of Rupture, Water Absorption and Thickness Swelling of two design sample of sandwich panel board then compare it mechanical and water resistance properties with conventional panel board. Process involved in sandwich panel board manufacture are manufacture of coconut fibre panel board and fiberglass panel board. The manufacturing of the sandwich panel board using layering method. Finally, testing of sandwich panel board sample which are Modulus Of Rupture, Water Absorption and Thickness Swelling. As result, non-reinforced sandwich panel board has MOR of 3.179MPa, WA of 46.5% and TS of 4.5%. For reinforced sandwich panel board, it has MOR of 7.096MPa, WA of 47.2% and TS of 8.3%. As comparison, the conventional panel board has MOR of 3.117MPa, WA of 61.3% and TS of 21.3%. In the nutshell, the result analyze that the non-reinforced sandwich panel board has the better result compared to conventional panel board and reinforced panel board that may be the best alternative for replacing traditional panel boards because it have a lot of economical potential.